PENGARUH PENGEMBANGAN KARIR DAN PROMOSI JABATAN TERHADAP SEMANGAT KERJA PEGAWAI PADA PENGADILAN AGAMA PALEMBANG - Widyta Rosadianti; Reva Maria Valianti; Reina Damayanti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
This research aims to test the hypothesis of the influence of career development and promotion on employee morale at the Palembang religious courts. The population in this study was all employees at the Palembang religious courts totaling 71 employees. The sampling technique uses purposive sampling, which means a technique for determining samples with certain considerations. The sample taken in this research was based on the number of Civil Servants (PNS) at the Palembang religious court, which was 54 employees. The collection method uses questionnaires and documentation. Data analysis techniques use simple linear regression, multiple linear regression, correlation coefficient analysis, coefficient of determination analysis, t hypothesis test and F hypothesis test with the help of SPSS 22. The results of the hypothesis test conclude that simultaneously there is a significant influence on the variables of career development and job promotion on morale Work. This can be seen from the F test, namely 0.000 < 0.05, which means that all independent variables jointly influence the dependent variable.